PERAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN EFESIENSI TRANSAKSI E-COMMERCE SHOPEE - Anisa Puspita; Dira Finanta; Cindy Rayani Ibrahim Sinulingga; Nurbaiti (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to analyze the role of digital technology in increasing the efficiency of Shopee e-commerce transactions. This research uses a qualitative method with a literature study approach from various sources relevant. The results of this research are that the presence of Shopee is becoming increasingly relevant along with the increasing use of digital technology in everyday life, especially in the context of e-commerce which allows people to carry out transactions without time and location limits. The use of digital technology on the Shopee platform really helps increase efficiency in e-commerce transactions. Shopee needs provisions regarding postage promotions to increase user conveniene